2017
DOI: 10.4102/sajim.v19i1.764
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the use of social media in the learning process

Abstract: Background: The study was established based on the inherent challenges of traditional learning systems, which require to be addressed. Arguably, social media can address many challenges of traditional learning if used properly. On this basis, it was important for the study to determine factors associated with the adoption of social media in learning.Objectives: This study determines the relationship between the ease of use and the usefulness of social media to its adoption. Moreover, it shows whether the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
3
14
0
1
Order By: Relevance
“…The research findings in this study indicate that because the social media landscape is continually changing through innovation, Internet users are increasing on a daily basis, and new users are more vulnerable to security concerns because they have less experience and low knowledge. This observation agrees with other studies which concluded that security was a concern, but it is important to educate users about important security issues to build confidence on these platforms (Lubua et al, 2017). Unforeseeable trends, businesses and NGOs will need a devoted social media department to succeed on these platforms.…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The research findings in this study indicate that because the social media landscape is continually changing through innovation, Internet users are increasing on a daily basis, and new users are more vulnerable to security concerns because they have less experience and low knowledge. This observation agrees with other studies which concluded that security was a concern, but it is important to educate users about important security issues to build confidence on these platforms (Lubua et al, 2017). Unforeseeable trends, businesses and NGOs will need a devoted social media department to succeed on these platforms.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…On the contrary, regardless of the negative experience that users of social media may have experienced, a well-planned use brings positive benefits to social society and the NGOs (Lubua et al, 2017). The research findings in this study indicate that because the social media landscape is continually changing through innovation, Internet users are increasing on a daily basis, and new users are more vulnerable to security concerns because they have less experience and low knowledge.…”
Section: Discussion Of Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…En lo referente al uso de redes sociales, el 93% de los padres de familia cuentan con perfiles en redes sociales, este dato permite identificar que que cada vez más padres están inmersos en el manejo de estos entornos tecnológicos y que no es necesario que desarrollen un uso fluido, sino que al menos ya tienen presencia en estos medios virtuales, lo que de alguna forma ayuda para que los jóvenes puedan tener orientaciones con criterios por parte de los adultos. Esto tiene una alta relación con estudios en diversos contextos geográficos (Siibak, Forsman y Hernwall, 2012;Park, 2016;Kristianto,2017;Lubua, Semlambo, y Pretorius 2017) que confirma muchos de los efectos sobre la actitud de los niños y jóvenes hacia las redes sociales, a partir de la influencia de los padres, entre otros aspectos, como la interacción con los pares, la facilidad de uso, el nivel de acceso, la experiencia de usuario y la consciencia de riesgo.…”
Section: Resultados Y Discusiónunclassified